Qualiy of life in displaced earthquake survivors - Lucia Savadori; Daniela Di Bucci; Mauro Dolce; Alessandro Galvagni; Alessia Patacca; Elena Pezzi; Giuseppe Scurci; Fabio Del Missier (Progress in Disaster Science)
Introduction: We investigated Quality of Life (QOL) in a sample of individuals (n = 341) who experienced different consequences in terms of displacement from their house after earthquake. Methods: Three groups were studied: those who had been displaced but are no longer so, those still displaced, and those who were never displaced. QOL for four time points was assessed: pre-earthquake, during displacement, at the time of the survey, and in ten years. Results: Different trajectories of QOL were observed in the three groups: not displaced individuals showed no significant variation, those who were displaced had a significant decline in QOL after the earthquake but a significant recovery after the displacement experience, and those who were still displaced at the time of the survey reported lowest QOL both after the earthquake and in the future, with no recovery. Predictors of perceived QOL decline were quality and type of temporary accommodation, place attachment, and perceived health impairment. Subsequent QOL perceived improvement was predicted by quality and type of temporary accommodation, risk awareness, and emotional well-being. Discussion: Our findings highlight the importance of minimizing the duration of temporary displacement and providing high-quality temporary accommodations, considering individual needs in the local contexts and communities.